Characterization of blaNDM–5-carrying plasmids in two clinical Salmonella isolates from Jiaxing city, China - Li, Ping; Yuan, Yongjuan; Yan, Yong; Jia, Miaomiao; Gao, Lei; Liu, Xuejuan; Sun, Yangming; Zhu, Guoying; Chen, Zhongwen (Frontiers in Microbiology, 2025)
IntroductionSalmonella is an important cause of foodborne diarrheal diseases worldwide. The emergence of blaNDM-positive carbapenem-resistant Salmonella enterica isolates in recent years poses a huge public health challenge.MethodsIn this study, two clinical S. enterica isolates carrying blaNDM–5: a serotype 4,[5],12:i:- strain (2023JX045) and a serovar Stanley strain (2024–406) were analyzed using antimicrobial susceptibility testing and whole genome sequencing.ResultsBoth isolates were multidrug resistant, with insusceptibility to ampicillin, ampicillin/sulbactam, amoxicillin/clavulanic acid, cefuroxime, ceftiofur, cefazolin, cefoxitin, cefotaxime, ceftazidime, cefepime, ceftazidime/avibactam, meropenem, imipenem, ertapenem, tetracycline, gentamicin, trimethoprim/sulfamethoxazole, florfenicol, chloramphenicol, ciprofloxacin, colistin, and polymixin B. The blaNDM–5-carrying plasmids in 2023JX045 and 2024–406 were named p23045-NDM5 and p2024406-NDM5, respectively, with both belonging to the incompatibility (Inc)HI2/IncHI2A group and sequence type ST3. In 2023JX045, blaNDM–5 was flanked by two same-oriented copies of IS26 elements (IS26-dsbC-trpF-bleMBL-blaNDM–5-IS5-ΔIS3000-ΔISKox3-umuC-umuD-IS26). In 2024–406, p2024406-NDM5 was found to carry two copies of blaNDM–5, possibly resulting from duplication of IS26-dsbC-trpF-bleMBL-blaNDM–5-IS5-ΔISAba125-ΔIS3000-ΔISKox3-umuC-umuD-IS26 and interrupted by mobile element IS1 at the upstream region of ΔIS3000.DiscussionThis is the first report to describe the presence of two blaNDM–5 copies on an IncHI2/IncHI2A plasmid carried by serovar Stanley, as well as the dissemination of blaNDM–5 in Salmonella in Jiaxing City, China. IS26-flanked composite transposons appeared to play an important role in the formation of this region. The dissemination of blaNDM in Salmonella isolates and the complexity of the blaNDM–5 region highlight the urgent need to monitor carbapenem-resistant S. enterica.